Village Consultative Institution Status of As a Form Of Democracy Life In The Village - Sundary, Rini Irianti; Januarita, Ratna; ., Irawati; Berliana, Erlyn; Yulistia, Intan (KnE Social Sciences, 2023)
Villages hold a prominent and expansive position in terms of sovereignty and their role in regulating and managing village affairs, as outlined in Law Number 6 of 2014 concerning Villages, Government Regulation Number 43 of 2014, and Government Regulation Number 76 of 2015, which pertain to the implementation of regulations stated in Law Number 6 of 2014 concerning Villages. Within the authority of the Village Head and members of the Village Representative Institution, one crucial aspect related to village governance is the existence of Village Regulations. These regulations play a vital role as they serve as the legal foundation for the implementation of various village programs and activities. As statutory regulations, Village Regulations are bound by formal and material principles that must be adhered to. Village regulations, as legal products, must align with the procedural techniques for creating legislation outlined in Law Number 12 of 2011 concerning the Establishment of Laws and Regulations. The process of formulating laws and regulations requires specific knowledge and skills that should be well understood by both the village government and the village community. Keywords: village, regulation, government